"Declension Comes Home": Cotton Mather, Male Youth Rebellion, and the Hope of Providential Affliction in Puritan New England. Issue 1 (18th June 2016) - Setran, David
Abstract: The theme of generational religious decline has been a staple of New England Puritan historiography. Yet while scholars have examined these issues at the larger cultural and ecclesial levels, few have looked at the small-scale manifestations of such "declension" within Puritan parent-child relationships. This article looks at Cotton Mather's perceptions of the causes of and potential solutions for male youth waywardness in colonial New England. Attempting to provide pastoral wisdom for distressed parents in his congregation, Mather also had to deal with this issue in his own home. His rebellious son, Increase, served as a very personal example of a vexing public issue, and Mather worked hard to put his pastoral ideals into "fatherly" practice. As he confronted these challenges, Mather located the causes of male youth rebellion in the perilous nature of "youth, " the failures of Puritan parents, and the inscrutable sovereignty of God. In the end, I argue that Mather was ultimately hopeful about God's work and purposes in the midst of youth declension. His belief in God's providence meant that the afflictions attending youthful rebellion could be perceived as God's means of spurring repentance and renewal, addressing parental sin, bolstering godly childrearing, and arousing youth themselves in the pursuit of righteousness.